A One-Season Prospective Study of Illnesses, Acute, and Overuse Injuries in Elite Youth and Junior Track and Field Athletes - Carragher, Paul; Rankin, Alan; Edouard, Pascal (Frontiers in Sports and Active Living, 2019)
Background: In high-level adult athletes, injury incidences and characteristics have been reported during international championships and during one season. Youth track and field athletes are also exposed to injury risk, although less information is available on this specific population, as well as on illness risk. Aim: To determine the prevalence of health problems (i.e. illnesses, acute and overuse injuries) in high level Youth and Junior Track & Field athletes. Method: During the 2015-16 athletics season (30 weeks from December 2015 to July 2016), we conducted a prospective cohort study on a population of Youth and Junior Irish national level athletes, during which athletes were asked to complete a weekly web-based questionnaire (Oslo Sports Trauma Research Center questionnaire on health problems) regarding their health problems. Results: A total of 70 athletes participated (37 male and 33 female athletes), with an average weekly response rate of 71%. The average weekly prevalence for all athletes was 27% (95%CI 17 to 38%) for all health problems, and 11% (95%CI 3 to 18%) for substantial health problems. Average prevalence varied significantly between endurance and explosive disciplines: a higher prevalence of all and substantial health problems and all and substantial overuse injuries was found in endurance disciplines. A higher prevalence of acute injuries was found in explosive disciplines. Characteristics of acute and overuse injuries differed according to sex and discipline: hamstring strain/cramps/spasms was the main injuries in explosive disciplines, and knee tendinopathy and lower leg strain/cramp/spasms in endurance disciplines, trunk cramps/spasms being frequent in both disciplines. Upper respiratory tract problems were the most commonly reported illnesses regardless of sex and disciplines. Conclusion: This study provides important information regarding the extent of health problem in Youth and Junior track and field athletes. This could help orient injury prevention measures. For injuries, it should be focused on muscle injuries, especially located on the hamstring, calf and trunk. For illness, prevention measures could include: screening tests for airway problems, but also general illness prevention measures (e.g. drinking regularly, eating ‘safe’ food, regular hand washing, decreasing contact with sick people, avoiding dehydration).